2015
DOI: 10.1126/science.aaa0709
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface properties and early activity of comet 67P/Churyumov-Gerasimenko

Abstract: Heat transport and ice sublimation in comets are interrelated processes reflecting properties acquired at the time of formation and during subsequent evolution. The Microwave Instrument on the Rosetta Orbiter (MIRO) acquired maps of the subsurface temperature of comet 67P/Churyumov-Gerasimenko, at 1.6 mm and 0.5 mm wavelengths, and spectra of water vapor. The total H2O production rate varied from 0.3 kg s(-1) in early June 2014 to 1.2 kg s(-1) in late August and showed periodic variations related to nucleus ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
238
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(273 citation statements)
references
References 14 publications
33
238
1
Order By: Relevance
“…Temperatures used in this study are lower than the surface temperatures reported by Capaccioni et al (2015) for measurements with the Rosetta-VIRTIS instrument. We assume the sublimation layer to be colder than the VIRTIS temperatures, which is consistent with their findings that the surface of 67P is almost free of ice and the significantly lower temperatures found by Gulkis et al (2015) below the surface. We further assume that the sublimating gas does not thermally accommodate to the top surface temperature while diffusing outward.…”
Section: Hydrodynamic Model (Bats-r-us)supporting
confidence: 89%
See 4 more Smart Citations
“…Temperatures used in this study are lower than the surface temperatures reported by Capaccioni et al (2015) for measurements with the Rosetta-VIRTIS instrument. We assume the sublimation layer to be colder than the VIRTIS temperatures, which is consistent with their findings that the surface of 67P is almost free of ice and the significantly lower temperatures found by Gulkis et al (2015) below the surface. We further assume that the sublimating gas does not thermally accommodate to the top surface temperature while diffusing outward.…”
Section: Hydrodynamic Model (Bats-r-us)supporting
confidence: 89%
“…This leads to total production rates of Q total = 8.7 × 10 25 s −1 −1.1 × 10 26 s −1 , depending on the illumination conditions. This is slightly higher than the observed total production rate of 4×10 25 s −1 for H 2 O in August 2014 as reported by Gulkis et al (2015). We note that we estimate the total production rate of 67P which only gives an upper limit for the H 2 O production rate.…”
Section: Increase In Production Ratecontrasting
confidence: 62%
See 3 more Smart Citations